2013
DOI: 10.1682/jrrd.2011.11.0213
|View full text |Cite
|
Sign up to set email alerts
|

Functional priorities, assistive technology, and brain-computer interfaces after spinal cord injury

Abstract: Spinal cord injury often impacts a person’s ability to perform critical activities of daily living and can have a negative impact on their quality of life. Assistive technology aims to bridge this gap to augment function and increase independence. It is critical to involve consumers in the design and evaluation process as new technologies, like brain-computer interfaces (BCIs), are developed. In a survey study of fifty-seven veterans with spinal cord injury who were participating in the National Veterans Wheel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(154 citation statements)
references
References 56 publications
2
149
0
3
Order By: Relevance
“…Although in the current study there was some agreement for the enhance, supplement and restore scenarios, with the statement The currently available hardware is cosmetically unappealing, this was not the case for replace, improve and research tool. For the statement The end-user image is stigmatized by the majority of paralyzed patients have a positive attitude towards implanted BCIs [15][16][17], especially if such a system were wireless [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the current study there was some agreement for the enhance, supplement and restore scenarios, with the statement The currently available hardware is cosmetically unappealing, this was not the case for replace, improve and research tool. For the statement The end-user image is stigmatized by the majority of paralyzed patients have a positive attitude towards implanted BCIs [15][16][17], especially if such a system were wireless [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving both healthy and disabled users, however, have found that 50-80% of the interviewed potential users were aware of BCIs before they completed the respective surveys [10,16,17]. Although it is conceivable that participants (i.e.…”
Section: Near Futurementioning
confidence: 99%
“…Despite the fact that the results of the case study show a high level of control, there is a critical issue with invasive BCIs: in a recent study, published by Blabe et al (2015), 40% of the respondents would not consider a neurosurgery at all, even if very good results could be expected [11]. In another study, conducted by Collinger et al (2013), non-invasiveness was also rated as a high priority [12].…”
Section: Introductionmentioning
confidence: 88%
“…In a survey related to brain-computer interfaces (BCIs), users indicated that they would prefer to control FES devices for arm and hand function or walking and standing rather than assistive devices like wheelchairs or robotic arm. 3 Essentially, people with SCI would prefer to restore function to their own limbs rather than augment function with external hardware.…”
Section: Fes To Restore Movementmentioning
confidence: 99%
“…A few studies have examined priorities for functional restoration as defined by individuals with SCI and found that restoration of arm and hand function is the top priority for individuals with tetraplegia. [1][2][3] Restoration of bladder and bowel function, as well as sexual function, is very important to people with a SCI at any level. Similarly, many people with SCI feel that restoration of walking and/or standing ability would have a positive impact on their quality of life.…”
Section: Introductionmentioning
confidence: 99%